Respuesta :
Answer:
Slope of Function B = – Slope of Function A
Step-by-step explanation:
Slope of function A=[tex]-2[/tex]
Slope of function B=$\frac{3-1}{3-2}=2$
Answer:
Slope of Function B = -Slope of Function A
Step-by-step explanation:
To find the right answer we need to calcultate the slope of each function.
Function A is [tex]f(x)=-2x+1[/tex]
From its expression we can deduct that its slope is [tex]m_{A} =-2[/tex] because the function is expressed in slope-intercept form where the coefficient of the x is the slope.
Now, function B is defined with a graph line, that intercepts points (-1,-5), (2,1) and (3,3). Using this points we can find its slope using the formula
[tex]m=\frac{y_{2}-y_{1} }{x_{2}-x_{1} } \\m_{B} =\frac{3-(-5)}{3-(-1)} =\frac{3+5}{3+1}=\frac{8}{4}=2[/tex]
So, function A has a slope of -2 and function B has a slope of 2.
Therefore, the last choice compares both slopes, because they are just opposite,
[tex]m_{B}=-m_{A}[/tex]
So, the answer is
Slope of Function B = -Slope of Function A